Evaluating the measurement properties and feasibility of physical activity and physical function assessments for children undergoing acute cancer treatmentKey points - Sarah L. Grimshaw; Nicholas F. Taylor; Rachel Conyers; Nora Shields (JSAMS Plus)
Background: As physical function and physical activity are often compromised among children and adolescents undergoing acute cancer treatment, psychometrically robust and feasible assessment tools are needed. The aim of this study is to evaluate the construct validity, responsiveness and feasibility of one physical activity assessment tool (Fitbit Inspire); and six physical function assessment tools (Movement ABC-2, Timed Up and Go, 30-s Chair Stand, Timed Rise from the Floor, Timed Up and Down Stairs, 6-min Walk Test) for children undergoing acute cancer treatment. Methods: A prospectively-registered, mixed methods, single-group study evaluated measurement properties against a priori hypothesis using Consensus-based Standards for the selection of health status Measurement Instruments (COSMIN) framework. Feasibility was assessed quantitively (a priori thresholds), and qualitatively (semi-structured interviews, focus-groups). Results: Twenty children/adolescents (median age 13 ​± ​5 years, various cancer diagnoses), 20 parents and 16 clinicians participated. Fitbit was feasible to assess daily steps only, had evidence of construct validity, tendency to overestimate step count and adequate evidence of responsiveness (compared to Actigraph). The 30-s Chair stand, 6-min Walk Test and Timed Up and Go were feasible and showed evidence of construct validity and responsiveness. To maximise feasibility, consideration of timing and intent of assessment are crucial. Conclusion: Fitbit has limitations as a physical activity assessment tool. The 30-s Chair Stand, 6-min Walk Test and Timed Up and Go were feasible to use and showed favourable measurement properties to assess physical function.